2021
DOI: 10.1038/s41598-021-85792-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of polyethylene glycol with cytochrome c investigated via in vitro and in silico approaches

Abstract: One of the significant proteins that have attracted research groups due to virtue of being a potent selective anticancer drug target and property of triggering apoptosis upon release in cytoplasm is cytochrome c (cyt c). The mechanical transformations due to the macromolecular crowding in membrane in the mammalian cell are proposed to be useful inductors of changes in volume. It is very interesting to know that mitochondrial function were observed to be improved by polyethylene glycol (PEG) interaction, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 99 publications
4
27
0
Order By: Relevance
“…Macromolecular crowding progressively is achieving acceptance in research, i.e., protein folding, therefore showing its nature of action as double-edged sword. The macromolecular crowding shows both destabilizing and stabilizing effects on protein structure, stability and function, depending upon size, shape and concentrations of crowder molecules as well as nature of the protein [ 15 , 19 , 31 , 38 , 57 , 58 , 59 , 60 , 61 , 62 ]. A few examples of proteins are examined in the crowded system (mixtures of crowders), where one molecule counteracts another, resulting in structural or/and thermal stabilization [ 14 , 20 , 48 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Macromolecular crowding progressively is achieving acceptance in research, i.e., protein folding, therefore showing its nature of action as double-edged sword. The macromolecular crowding shows both destabilizing and stabilizing effects on protein structure, stability and function, depending upon size, shape and concentrations of crowder molecules as well as nature of the protein [ 15 , 19 , 31 , 38 , 57 , 58 , 59 , 60 , 61 , 62 ]. A few examples of proteins are examined in the crowded system (mixtures of crowders), where one molecule counteracts another, resulting in structural or/and thermal stabilization [ 14 , 20 , 48 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The negatively charged macromolecules, shape and size of molecules, charges on the surfaces of pathways which acts as switches to regulate cytoplasmic transport of ions and pools having unequal “bulk” concentrations of ionic metabolites are just a few of such theories [ 37 ]. As a result, in crowded cellular conditions, the importance of various types of interactions, which play a significant role in protein folding to maintain structure and function, cannot be ignored [ 15 , 25 , 45 , 63 , 64 ]. In vitro crowding assays are now being designed with proteins, which better reflect bio-macromolecular environments under in vivo, allowing for hydrophobic bonding and screened electrostatic interactions [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang and coworkers indicated that the increase in the residual activity of lysozyme was ascribed to the fact that the addition of PEG suppressed enzyme aggregation via a strong PEG–protein interaction and stabilized the protein secondary structure somewhat [ 6 ]. On the contrary, soft interactions with PEG were also observed to induce structural changes and destabilize proteins [ 28 , 31 , 32 , 33 , 34 ]. For the nucleic acids, low molecular weight PEGs were observed to decrease their thermodynamic stability, while high molecular weight PEGs showed the opposite [ 35 ].…”
Section: Introductionmentioning
confidence: 99%